Strengthening the Indonesian Notaries’ Authority in Legalizing Apostille Documents - Ali Abdullah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
As public officials, notaries are given the authority to make authentic deeds and legalize documents signed in the presence of a notary. The Minister of Law and Human Rights Regulation, No. 6 of 2022 Article 2, Paragraph 3, Letter d states that one of the recognized convention state documents is a document issued by a notary. The research applied a normative juridical method. This research links the authority of notaries as public officials in the Apostille legalization service process following the enactment of the Apostille Convention in Indonesia in October 2021. The study reveals the government policy of legalizing Apostille documents by notaries. The results show that notaries, as public officials, have the authority to carry out legalization. Still, after the Apostille Convention enactment, the law regulates explicitly Apostille. Still, it does not explain the legalization process by a notary to obtain an apostille certificate. Hence, the study concludes that no regulation regarding the legalizing of apostille documents by a notary brings implications for the notary’s role in obtaining legal protection and certainty.